Exploring Reflective Learning for A Design Thinking Class - Ekarina Ekarina; Engliana Engliana (Yayasan Visi Intan Permata, 2025)
This research explores reflective learning as a potential tool to enhance students’ learning experience in a Design Thinking class for English Language Education majors. Specifically, the researchers seek (i) to share how reflective learning can be implemented in a Design Thinking class; and (ii) to investigate ways in which the implemented reflective learning have affected students in processing, evaluating and improving their lesson plan design. To do this, this article lays out the class design that the researchers have implemented in their own Design Thinking classroom; this is carefully mapped out to Gibb’s reflective cycle to show how the step-by-step design is aligned with reflective teaching practices. Additionally, students’ reflective activities, including consultations with the instructor, teaching demo evaluation rubrics, and reflective essays are analyzed using thematic analysis to uncover insights into their learning process and outcomes. The study reveals that the implemented reflective learning steps help students achieve the intended results: (a) successful revision of their lesson plan; and (b) in-depth reflection throughout the whole process that have influenced their professional values and approach as future educators beyond the Design Thinking class.